CO2 emission reduction potential of large-scale energy efficiency measures in heavy industry in China, India, Brazil, Indonesia and South Africa - Daisuke Hayashi; Matthias Krey (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2005)
We quantify the theoretical potential for CDM projects to improve energy-efficiency in selected heavy industrial sectors (iron and steel, cement, aluminium, pulp and paper and ammonia) in China, India, Brazil, Indonesia and South Africa and discuss the likelihood of the potential emission reductions materialising under CDM. Promising project types are: near net shape casting and pulverized coal / natural gas injection in iron and steel, cement blending, changes in aluminium smelter technology from Söderberg to prebaked anodes, continuous digestion process in pulp and paper, complete process integration in ammonia production. The total annual emission reduction potential of the iron and steel, cement and aluminium could reach more than 800 million CERs for China, India, Brazil and South Africa. While industrial boiler refurbishment could be widely replicated, reductions per boiler are relatively limited and overall potential is difficult to estimate.
Keywords: 330; CDM; heavy industry; efficiency improvement